Circuito agroturístico para el desarrollo del turismo rural en el cantón Bolívar, provincia de Manabí - Álava Chichanda, Karen Andrea (2015)
The rural tourism is a new form that it is passing to new development alternatives. It is for this reason that research with the aim of promoting agro tourism activities to develop socio-economic of the Bolívar canton has been. For this there was done in the first instance a diagnostic tourist agriculture of the sector where there was realized an inventory of 6 rural resources of the canton, determining the grade of tourist potential of each of them, likewise there was realized an inventory of 21 agricultural farms inside the canton, Later there was announced the type of tourist, basic infrastructure and the services of the circuit. Also there decided the fortitude, opportunities, weaknesses and threats of the agriculture tourism. Likewise by means of compiled information there decided the characteristics of the demand in which it was possible to determine the profile as a whole with the requests and needs of the visitor. By means of the raised there was realized the design of the product that gave like turned out two circuits agriculture tourist of the canton, the cattle one and another cacaotero, which it consists of 11 farms with major potential. Also is the study of environmental impact and mitigation strategies were generated through this. Once the strategies you proceeded to carry out the timelines and costeos circuits and as a last point were marketing and distribution strategies of the same through which was created a logo and slogan of the circuit and different types of presentation in promotional items and advertising printing.